تفعيل المقاصد الشرعية على الوقاية من الأمراض المعدية: فيروس كورونا نموذجا: ACTIVATING OF MAQĀṢID SHARIA ON PREVENTING INFECTIOUS DISEASES: CORONA VIRUS AS A MODEL (International Seminar on Syariah and Law (INSLA), 2020)
The study aims to activate of Maqāṣid Sharia on preventing infectious diseases (Corona Virus as a model). The research problem of this study enables the occurrence of the Coronavirus, which is a type of infectious disease that has spread all over the world and drawn the attention of all nations about it. Due to the severity of the conditions accompanying the pandemic, and its impact on public life and private rituals, it is a crucial to call for a jurisprudential position from specialists and original research both scholars and seekers of knowledge. That is because if the issue is left without answer, it would lead to a harm and never-ending debate among the people. Based on the recent conditions of the pandemic which sees the increasing numbers of infections and deaths as a result of the outbreak of this virus on a daily basis around the world, and the spread of the pandemic among societies, this research attempted to conduct an original study on the prevention of this type of infectious disease by activating the objectives of Sharia. Therefore, this research aims to clarify the activation of the five Sharia objectives which are referred to in preventing infectious diseases and stopping their spread to societies because the threat to humans does not distinguish color, gender, and belief. This research used an inductive approach to analyze the data collected. Among results of the research are: the prevention of diseases and illnesses before their occurrence and treatment after their occurrence is imperative to save lives and souls from perdition, and preserving the human soul is one of the basic objectives of the Sharia that includes the five objectives. The purpose of preserving religion is the role of preachers on faith awareness, and the purpose of preserving life is the role of doctors on health awareness, and the purpose of preserving the mind is the role of writers on intellectual awareness, and the purpose of preserving the children (lineage) is the role of fathers on family awareness, while the purpose of saving wealth is the role of experts on economic awareness. يتناول هذا البحث موضوع تفعيل المقاصد الشرعية على الوقاية من الأمراض المعدية (فيروس كورونا نموذجًا)، حيث تكمن مشكلة البحث في وقوع فيروس كورونا وهو نوع من أنواع الأمراض المعدية التي عمت أرجاء الأرض والتفتت إليها أنظار الأمم؛ لشدة الأحوال المرافقة لها وتأثيرها على الحياة العامة والعبادات الخاصة تستدعي موقفًا فقهيًا من أهل الاختصاص وبحثًا أصيلاً من طلبة العلم يترتب على ترك بيانها والبحثُ فيها ضررٌ وجدل مستمر مقيت بين عامة الأمة. فنظراً لازدياد عدد الإصابات والوفايات نتيجة تفشي جائحة فيروس كورونا يوماً بعد يوم في كلّ أنحاء العالم، وبالإضافة إلى انتشار هذا المرض على المجتمعات، حاول هذا البحث تناول دراسة تأصيلية للوقاية من نوع هذه الأمراض المعدية بتفعيل مقاصد الشريعة. وبناء على ذلك، يهدف هذا البحث إلى توضيح تفعيل المقاصد الشرعية الخمسة التي يُعتمد عليها في موضوع الوقاية من الأمراض المعدية ووقف انتشارها على المجتمعات لأنها تهدد البشرية دون تفريق بين لون أو جنس ومعتقد. وقد اعتمد هذا البحث في دراسة الموضوع على المنهج الاستقرائي التحليلي. ومن أبرز نتائج البحث؛ أن الوقاية من الأمراض والأسقام قبل حدوثها وبالتدواي بعد حدوثها، أمر لابد منه لأجل إنقاذ الأرواح والأنفس من الهلاك، والحفاظ على النفس البشرية من مقاصد الشريعة الأساسية التي هي ضمن الضروريات الخمس. فمقصد حفظ الدين بدور الخطباء على التوعية الإيمانية، ومقصد حفظ النفس بدور الأطباء على التوعية الصحية، ومقصد حفظ العقل بدور الأدباء على التوعية الفكرية، ومقصد حفظ النسل بدور الآباء على التوعية الأسرية، ومقصد حفظ المال بدور الخبراء على التوعية الاقتصادية